Immobilization of Laccase on Magnetic Chelator Nanoparticles for Apple Juice Clarification in Magnetically Stabilized Fluidized Bed - Wang, Feng; Owusu-Fordjour, Mariam; Xu, Ling; Ding, Zhongyang; Gu, Zhenghua (Frontiers in Bioengineering and Biotechnology, 2020)
The juice clarification, one of the key steps in juice processing, is suffered from haze formation resulted from residual phenolic compounds. In this study, laccase was immobilized on metal-chelated magnetic silica nanoparticles and used for continuous juice clarification in magnetically stabilized fluidized bed (MSFB) assisted by alternating magnetic field. Furthermore, a new combination of laccase catalysis and microfiltration was developed for the juice clarification. Immobilized laccase provided high relative activity within broader ranges of pH and temperature compared to the free enzyme. Magnetic immobilized laccase exhibited the best reaction rate of 12.1 μmol g-1 min-1 for catechol oxidation under the alternating magnetic field of 400 Hz, 60 Gs. No activity loss occurred in immobilized laccase after 20 h continuous operation of juice treatment in MSFB under alternating magnetic field. Combined with microfiltration after treatment with immobilized laccase, the color of apple juice was decreased by 33.7% and the light transmittance was enhanced by 20.2%. Furthermore, only 16.3% of phenolic compounds and 15.1% of antioxidant activity was reduced for apple juice after the clarification. By this combination strategy, the apple juice possessed good freezing-thaw and thermal stability.